2014
DOI: 10.5530/fra.2014.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity and free radical scavenging potential of alpha lipoic acid and quercetin against Al2O3 nanoparticle-induced toxicity in mice

Abstract: Introduction: Exposure to nanomaterials (NPs) may lead to enhanced generation of free radicals and failure of endogenous antioxidant defense system ultimately resulting in oxidative stress. The present study aimed to evaluate the comparative efficacy of alpha lipoic acid (ALA) and quercetin, the two antioxidants against aluminium oxide nanoparticle induced oxidative stress. Methods and Materials: Male swiss albino mice were exposed to aluminum oxide NPs for seven days and were co-administered orally with querc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Aluminum oxide nanoparticles (Al 2 O 3 NPs) have been involved in many manufacturing purposes, including packaging materials, cutting tools, refractory products, cosmetic fillers, and semiconductor materials (Yousef et al 2019 ). The Al 2 O 3 -NPs exposure considerably raised ROS release, while the hepatic-reduced glutathione (GSH) levels, catalase, and superoxide dismutase (SOD) activities were decreased (Shrivastava et al 2014 ). Suppression of hepatic expression of peroxisome proliferator-activated receptor gamma-coactivator 1α (PGC-1α) and mitochondrial transcription factor A (mtTFA) gene was also confirmed with Al 2 O 3 -NPs exposure (Yousef et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Aluminum oxide nanoparticles (Al 2 O 3 NPs) have been involved in many manufacturing purposes, including packaging materials, cutting tools, refractory products, cosmetic fillers, and semiconductor materials (Yousef et al 2019 ). The Al 2 O 3 -NPs exposure considerably raised ROS release, while the hepatic-reduced glutathione (GSH) levels, catalase, and superoxide dismutase (SOD) activities were decreased (Shrivastava et al 2014 ). Suppression of hepatic expression of peroxisome proliferator-activated receptor gamma-coactivator 1α (PGC-1α) and mitochondrial transcription factor A (mtTFA) gene was also confirmed with Al 2 O 3 -NPs exposure (Yousef et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, neurotoxicological effects have been observed leading to the formation of neurodegenerative and immunosuppressive effects. Another in vivo study by Shrivastava et al [39] suggested that Al 2 O 3 -NPs induce a high level of oxidative stress followed by high ROS concentration, reduced levels of GSH, and low CAT and SOD activities, in mice during 7 days of an oral application. The hepatorenal toxicity of Al 2 O 3 -NPs and ZnO-NPs was monitored by Yousef et al [43], showing that both NPs exerted significant toxicity but also synergistic toxicological effect on the liver and kidneys accompanied by systemic inflammation.…”
Section: Toxicological Effects Of Various Nanoparticlesmentioning
confidence: 99%
“…In the global market of NPs, the alumina nanoparticles (Al 2 O 3 -NPs) are represented around 20% [17]. The purpose of their use is diverse, from application in medicine (for site-specific 3 Oxidative Medicine and Cellular Longevity drug delivery), orthopedic implants, cosmetics, food industry, chemical engineering, catalysis, resistant coatings, lithium batteries, and all the way to jet and rocket fuels [22,39,40]. They also have been used in weapons, munitions, and explosives; in propeller shafts as surface coatings; also as scratch and abrasive-resistant coatings on sunglasses; and in the car industry [41].…”
Section: Toxicological Effects Of Various Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations